O peão de trecho e o peão de casa: identidade operária entre os trabalhadores da construção civil de Barcarena no canteiro de obras da ALBRAS/ALUNORTE - FONTES, Edilza Joana Oliveira (2012)
This article intends to discuss the relations among the ALBRAS/ALUNORTE and the syndical organization process of Barcarena civil construction workers, at the moment of the ALBRAS plant construction. The work relations has been analyzed in the work area and discussed the both modernity and progress ideas whose workers express during the moments conflicts with the civil construction contractor, with the Pará Government as well as the region development project, in the strikes occurred over the 1984 and 1985 period.